«Wir haben jetzt die Demokratie, das ist kompliziert genug». Zur Krise demokratischer Systeme und Auflösung des Politischen in «Munin oder Chaos im Kopf» von Monika Maron: [«Now we have democracy, that is complicated enough». On the crisis of democratic systems and the decline of politics in «Munin or Chaos in the Head» by Monika Maron] (Studia theodisca, 2021)
In the light of the profound changes that have affected both the political scenario and the political role and forms of engagement of literature over the past thirty years, Monika Maron’s novel Munin oder Chaos im Kopf (2018) seems particularly topical. If analysed through Hannah Arendt’s remarks on the nature of politics and Zygmunt Bauman’s thoughts on our “besieged” society, the narrator’s shocking experience can be seen as both the consequence and the reflection of a failure of our democratic systems, as well as of our traditional idea of politics itself.